2022
DOI: 10.1038/s41598-022-07759-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid DNA origami nanostructure detection and classification using the YOLOv5 deep convolutional neural network

Abstract: The intra-image identification of DNA structures is essential to rapid prototyping and quality control of self-assembled DNA origami scaffold systems. We postulate that the YOLO modern object detection platform commonly used for facial recognition can be applied to rapidly scour atomic force microscope (AFM) images for identifying correctly formed DNA nanostructures with high fidelity. To make this approach widely available, we use open-source software and provide a straightforward procedure for designing a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Deep learning research has been reported in many fields, including medicine [8,[11][12][13][14][15][16][17]. In cytology, several formidable barriers need to be overcome to achieve widespread adoption, such as preimaging collection and preparation factors.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning research has been reported in many fields, including medicine [8,[11][12][13][14][15][16][17]. In cytology, several formidable barriers need to be overcome to achieve widespread adoption, such as preimaging collection and preparation factors.…”
Section: Introductionmentioning
confidence: 99%
“…YOLOv5 is a kind of CNN with the inherent network composition structure of a traditional CNN, including the input layer, convolution layer, and pooling layer. In addition, it also adds new network composition modules [ 41 , 42 ]. The structure of YOLOv5 is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Manual analysis through counting not only is tedious but can also inject bias into the analysis. Machine learning tools are being developed to facilitate high-throughput quantitative evaluation of DNA nanostructures through AFM analysis (Figure A) …”
Section: Characterization Of Dna Nanostructuresmentioning
confidence: 99%
“…(A) Machine-learning enabled high-throughput analysis of a heterogeneous mix of DNA origami structures comprised of triangle, rectangle, and “imposter” DNA cylinders. The YOLO-v5 trained neural network successfully identified the triangles (blue boxes) and rectangles (red boxes) and dismisses the cylinders . (B) Imaging of unstained DNA origami nanoplates on commercial carbon films.…”
Section: Characterization Of Dna Nanostructuresmentioning
confidence: 99%